Study of Jewel Bugs (Hemiptera: Scutelleridae) of Hilly Regions of Nepal - K.C., Sajan; Khadka, Anjali; Kafle, Kapil (Journal of the Plant Protection Society, 2018)
A survey of jewel bugs (Hemiptera: Scutelleridae) was conducted in three hilly districts of Nepal viz. Tanahun, Lamjung and Kaski, over a period of 13 months (April 2017-May 2018). The prime purpose of the research was to find out the Scutelleridae diversity in these districts which hasn’t been done before. Raipur village of Tanahun, Sundarbazar, Kunchha and Dura Daanda areas of Lamjung and Hemja and Sarangkot areas of Kaski were explored for this purpose. A total of 31specimens of Scutelleridae were collected at localities with altitude varying from 700-1600 masl. Four different species of jewel bugs from 1 subfamily, 1 tribe and 3 genera were recorded. All the species fell under single subfamily Scutellerinae Leach, 1815 and tribe Scutellerini Leach. The recorded species are Chrysocoris patricius, Chrysocoris pulchellus, Eucorysses grandis and Poecilocoris nepalensis. All species were recorded for the first time from the studied areas.